2021
DOI: 10.1186/s12876-021-01969-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of LigaSure Hemorrhoidectomy in the Elderly Population: A retrospective cohort study

Abstract: Background This study aims to assess the association between age and outcomes in patients undergoing hemorrhoidectomy. Methods This is a population-based cohort study. A retrospectively collected database with consecutive patients whose symptomatic prolapsed hemorrhoids managed by the LigaSure hemorrhoidectomy between Jan. 2015 and May 2017 was reviewed. Among 1238 patients, 1075 were under 65 years old (group 1), and 163 were 65 years old or older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Other authors reported that age was not a risk factor for complications after hemorrhoidal surgery. 36,37 In a study by Yamamoto et al, 38 the total number of adverse events after hemorrhoidectomy was higher in the nonelderly group (21% vs 6%), but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 94%
“…Other authors reported that age was not a risk factor for complications after hemorrhoidal surgery. 36,37 In a study by Yamamoto et al, 38 the total number of adverse events after hemorrhoidectomy was higher in the nonelderly group (21% vs 6%), but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 94%
“…Some publications recommend pedicle saturation to reduce bleeding caused by the opening of the wound edges in LigaSure hemorrhoidectomy, as the incidence of delayed bleeding ranges from 0.9% to10%. 22,23 Over the long term, the recurrence rate of the disease is higher for minimally invasive techniques developed with technology compared to surgical hemorrhoidectomy. In our study, the recurrence rate was 9.4% for the laser-treated group and 2.5% for the LigaSure hemorrhoidectomy group, indicating that surgical treatment remains the gold standard treatment for hemorrhoidal disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the bleeding amount during the operation was significantly lower for the laser group (4.8 mL) compared to the LigaSure group (15.5 mL). Some publications recommend pedicle saturation to reduce bleeding caused by the opening of the wound edges in LigaSure hemorrhoidectomy, as the incidence of delayed bleeding ranges from 0.9% to10% 22,23 …”
Section: Discussionmentioning
confidence: 99%